Simultaneous and sensitive determination of the main metabolites of the plasticizer DEHP and its substitutes DEHTP, DINCH and TEHTM in human urine by coupling of on-line SPE, UHPLC and tandem mass spectrometry - Kuhlmann, Laura; Muench, Frank; Göen, Thomas; Eckert, Elisabeth (Analytical Methods, 2022)
With the prominent but toxicologically critical plasticizer di-(2-ethylhexyl) phthalate (DEHP) declining, alternative plasticizers are increasingly used leading to a continuously more diverse exposure situation of humans with multiple plasticizers. Therefore, an on-line SPE-LC-MS/MS method for the simultaneous determination of the most relevant urinary biomarkers of exposure to DEHP and the alternative plasticizers 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINCH), di-(2-ethylhexyl) terephthalate (DEHTP) and tri-(2-ethylhexyl) trimellitate (TEHTM) was developed. The method is characterized by a high sensitivity with limits of detection ranging from 0.006 to 0.047 mu g L-1 combined with an easy and straightforward sample preparation procedure. The wide linear working range of the method enables a reliable determination of analyte background levels in the general population as well as its potential use for monitoring studies investigating elevated plasticizer exposure settings. The method was successfully applied to urine samples from ten volunteers without occupational exposure to plasticizers revealing ubiquitous background exposure levels of the common plasticizers DEHP, DEHTP and DINCH.
CRIS-Team WoS Importer:2022-10-14